Prostrate-specific antigen level following 120W Green light High Performance System Laser Photoselective Vaporisation Prostatectomy (PVP) & its efficacy and safety of PVP in Benign Prostatic Hyperplasia (BPH) - Gawali Santosh Raghunath; Kranti Santosh Sorte Gawali; Avinash Namdeo Jadhao (SVU - International Journal of Medical Sciences, 2023)
Background: The Green Light Laser HPS 120W is a widely used procedure nowadays. The latest machines offer major improvements on the first prototypes in terms of speed, efficiency, safety and total PSA and f/t PSA ratio changes postoperatively in BPH patients after using GREENLIGHT HPS 120W. Objectives: The objective of this study was to analyse the safety, and efficacy of the new technology, the HPS- 120W Green Light Laser in the management of patients who were symptomatic because of BPH postoperatively Patients and methods: A total of 38 patients who underwent the Green Light Laser PVP at our institution were studied. Serum prostrate-specific antigen level changes were observed postoperatively after 1 month. Results: The average age of the patients was 63.93 years, range 58-72. The Total average IPSS score was 21.88, range of 18-27. The average PSA level of patients in our study after 1month was 2.25ng/dl and prostate size of 65.82ml. An average IPSS score measured after 1 month of surgery was 10.05 with a range of 7-13, drop in IPSS score was 11.83 (21.88-10.05) while the average PVR measured after 1 month of surgery was 29.82ml with a range of 18-45ml and average Q max measured after 1 month of surgery was 20.55ml/s with a range of 17.8-24.7ml/s, an increase in Q max was 12.56ml/s (20.55-7.99). Conclusions: Our study shows that the Green Light HPS 120W Laser is safe and efficacious for the management of BPH.